The Two Faces of Consciousness: Review of S. Blackmore, Consciousness: An Introduction - FARBER, Ilya (Institutional Knowledge at Singapore Management University, 2003)
Reviews the book 'Consciousness: An Introduction', by Susan Blackmore.